Akibat Hukum Pembatalan Akta Hibah Yang Dibuat Di Bawah Tangan Dan Tanpa Persetujuan Ahli Waris Lainnya (Lex Jurnalica, 2023)
A grant is a gift made by a person to another party made while still alive and the implementation of the distribution is usually done when the grantor is still alive. In Article 1682 of the Civil Code "the method or process of granting must go through a Notary Deed where the original Minuta is kept by the Notary concerned and if it is not carried out then the Grant becomes invalid and cancelled". This research was conducted using normative legal research methods. The first problem that the author will discuss is what are the legal consequences for canceling a grant deed made underhanded and without the consent of other heirs?, secondly, how is the legal force of a grant deed made underhanded?, thirdly, what are the provisions and methods of calculating grant tax on transfers? land and buildings? From the results of this study, conclusions can be drawn and it is hoped that the deed of grant made before the official making the land deed (PPAT) is a statement of the existence of a legal act and as a means of proof. And before making the deed of grants, obtain approval from other heirs so that problems do not arise in the future which will harm the parties.